ANALISIS MAKNA KULTURAL PADA PROSESI PERNIKAHAN ADAT BUGIS: KAJIAN ETNOLINGUISTIK - Nasution, Muhammad Muslim; Vahlepi, Sahrizal; Sholihah, Mar’atun; Izar, Julisah (Universitas Hamzanwadi, 2025)
This research aimed to explain in detail the cultural meaning of the Bugis traditional wedding procession. This research only focuses on analyzing cultural meanings at the pre-wedding stage and during marriage during the Bugis traditional wedding procession. This type of research is descriptive research with a qualitative approach. The data collection techniques in this research are interview, recording and note taking techniques and the data analysis technique in this research uses flowing data analysis techniques. The results of the research found 21 objects and activities that were interpreted culturally and 17 objects and activities that were interpreted culturally where the cultural meaning was related to belief and contained noble values ​​that were guarded and preserved by the Bugis community.